ChemInform Abstract: Development of an Efficient Route to CF3‐Substituted Pyrrolopyrimidines Through Understanding the Competition Between Michael and aza‐Henry Reactions. Issue 24 (June 2015) - Tkachuk, V. M.; Sukach, V. A.; Kovalchuk, K. V.; Vovk, M. V.; Nenajdenko, V. G.
Abstract: The regioselective addition of nitromethane to 2‐oxo‐4‐trifluoromethyl‐1, 2‐dihydropyrimidine‐5‐carboxylates is elaborated.